Introduction to financial services marketing - Harrison, Tina (Henry Stewart Talks, 2008)
Role and contribution of the financial services sector, Key trends and challenges |Drivers of change, Regulations, Technological developments, General competitive trends, Strategic responses, From customer acquisition to retention, Demutualization, From specialization to generalization, Trend towards product bundling, Arms length distribution, Trend towards charging